The Harmonization of Polygamy Between Islamic Law and Legal Law in Indonesia - Ma'u, Dahlia Haliah (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2023)
Polygamy as a solution for married couples who have certain problems still leaves a number of problems among Indonesian Muslims. The legal norms governing polygamy have become meaningless with the rise of unrecorded polygamy by certain people who find it difficult to practice polygamy formally in Indonesia. The dichotomy of Islamic law and legal law often triggers this problem, which is always up to date, even though these two norms can be synchronized by adopting the values of benefit which are not partial to husband and wife. This article aims to describe the harmonization of polygamy between Islamic law and legal law in Indonesia. The method this research used was library research with qualitative descriptive analysis. The theory that researchers use refers to several Islamic legal rules and regulations in Indonesia regarding polygamy. The findings of this research are that together between Islamic law and legal law in Indonesia have regulated the permissibility of polygamy with the main requirement being that the husband is able to be fair. This requirement becomes a guideline for wives to allow their husbands to practice polygamy. It is the husband and wife who can measure the fulfillment of these main requirements, and this is where the harmonization of the two regulations in Indonesia lies. The researcher found that the most dominant dichotomy between the two legal norms lies in not allowing female civil servants to become second, third, or fourth wives, as regulated in Article 4 paragraph 2 PP.45/1990. This rule is not in sync with the norms of Islamic law which do not prohibit this from being done. Therefore, it is necessary to revise the state legal norms regarding polygamy for the benefit of all elements of family and society.